OP0005 ELEVATED STAT1 EXPRESSION BUT NOT PHOSPHORYLATION IN LUPUS B CELLS CORRELATES WITH DISEASE ACTIVITY AND INCREASED PLASMABLAST SUSCEPTIBILITY. (2nd June 2020) - Aue, A.; Szelinski, F.; Weißenberg, S.; Wiedemann, A.; Rose, T.; Lino, A.; Dörner, T.
Abstract : Background: Systemic lupus erythematosus (SLE) is characterized by two pathogenic key signatures, type I interferon (IFN) (1.) and B-cell abnormalities (2.). How these signatures are interrelated is not known. Type I-II IFN trigger activation of Janus kinase (JAK) – signal transducer and activator of transcription (STAT). Objectives: JAK-STAT inhibition is an attractive therapeutic possibility for SLE (3.). We assess STAT1 and STAT3 expression and phosphorylation at baseline and after IFN type I and II stimulation in B-cell subpopulations of SLE patients compared to other autoimmune diseases and healthy controls (HD) and related it to disease activity. Methods: Expression of STAT1, pSTAT1, STAT3 and pSTAT3 in B and T-cells of 21 HD, 10 rheumatoid arthritis (RA), 7 primary Sjögren's (pSS) and 22 SLE patients was analyzed by flow cytometry. STAT1 and STAT3 expression and phosphorylation in PBMCs of SLE patients and HD after IFNα and IFNγ incubation were further investigated. Results: SLE patients showed substantially higher STAT1 but not pSTAT1 in B and T-cell subsets. Increased STAT1 expression in B cell subsets correlated significantly with SLEDAI and Siglec-1 on monocytes, a type I IFN marker (4.). STAT1 activation in plasmablasts was IFNα dependent while monocytes exhibited dependence on IFNγ. Conclusion: Enhanced expression of STAT1 by B-cells candidates as key node of two immunopathogenic signatures (type I IFN and B-cells) related to important immunopathogenic pathways and lupus activity. We show that STAT1 is activated upon IFNα exposure in SLE plasmablasts. Thus, Jak inhibitors, targeting JAK-STAT pathways, hold promise to block STAT1 expression and control plasmablast induction in SLE. References: [1]Baechler EC, Batliwalla FM, Karypis G, Gaffney PM, Ortmann WA, Espe KJ, et al. Interferon-inducible gene expression signature in peripheral blood cells of patients with severe lupus. Proc Natl Acad Sci U S A. 2003;100(5):2610-5. [2]Lino AC, Dorner T, Bar-Or A, Fillatreau S. Cytokine-producing B cells: a translational view on their roles in human and mouse autoimmune diseases. Immunol Rev. 2016;269(1):130-44. [3]Dorner T, Lipsky PE. Beyond pan-B-cell-directed therapy - new avenues and insights into the pathogenesis of SLE. Nat Rev Rheumatol. 2016;12(11):645-57. [4]Biesen R, Demir C, Barkhudarova F, Grun JR, Steinbrich-Zollner M, Backhaus M, et al. Sialic acid-binding Ig-like lectin 1 expression in inflammatory and resident monocytes is a potential biomarker for monitoring disease activity and success of therapy in systemic lupus erythematosus. Arthritis Rheum. 2008;58(4):1136-45. Disclosure of Interests: Arman Aue: None declared, Franziska Szelinski: None declared, Sarah Weißenberg: None declared, Annika Wiedemann: None declared, Thomas Rose: None declared, Andreia Lino: None declared, Thomas Dörner Grant/research support from: Janssen, Novartis, Roche, UCB, Consultant of: Abbvie, Celgene, Eli Lilly, Roche, Janssen, EMD, Speakers bureau: Eli Lilly, Roche, Samsung, Janssen